Association between Pregnancy-Associated Diabetes and Macrosomia: A Systematic Review and Meta-analysis - Salah Faaez Abdulnabi; Omid Nikpayam; Mostafa Mohammadi; Ali Jabbari; Somayeh Ghorbani Gholiabad; Hamed Abedalnabi Flaifel; Sarah Ali Alatter (Journal of Clinical and Basic Research)
Background: Diabetes mellitus (DM) is a major challenge for public health worldwide. Pre-existing diabetes and gestational diabetes (GDM) are linked to poor outcomes in pregnancy, perinatal and maternal. Research indicates that GDM has become significantly more prevalent in several countries, increasing by over 30%. Glycemic control in women during pregnancy plays a major role in the health status of the mother and fetus. Macrosomia is one of the most critical adverse outcomes of DM, which results in negative consequences for the health of infants. This systematic review and meta-analysis study aimed to investigate the association between pregnancy diabetes and macrosomia in infants. Methods: A comprehensive systematic search was conducted in electronic databases, from inception up to August 2024 to obtain related studies. Two independent researchers evaluated the studies based on the objectives of the study. The pooled effect size was computed using pooled odds risks (ORs) with 95% confidence intervals (CIs). Additionally, we conducted publication bias assessments, sensitivity analyses, and subgroup analyses. The statistical analysis incorporated twelve studies. Quality assessment of included studies was conducted using the Newcastle-Ottawa Scale (NOS). Results: Statistical analysis in the present study on the pregnant diabetic mother and infants with macrosomia demonstrated a direct significant association between DM and macrosomia (OR: 2.94, 95% CI: 2.06-4.20, P <0.0001) and (OR: 8.17, 95% CI: 4.85-13.75, P<0.0001), respectively. Sub-group analysis revealed subjects with pre-gestational diabetes against GDM, had a greater risk of delivering an infant with macrosomia. Conclusion: The results revealed a significant association between all three types of GDM. All three types of diabetes can lead to macrosomia, but pre-gestational diabetes has a more significant positive relationship with macrosomia. However, improving lifestyle can be considered as key strategy against macrosomia and associated diabetic complications.